2020
DOI: 10.1038/s41419-020-03029-0
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MNX1-AS1 promotes progression of intrahepatic cholangiocarcinoma through the MNX1/Hippo axis

Abstract: Long non-coding RNAs (lncRNAs) have extremely complex roles in the progression of intrahepatic cholangiocarcinoma (ICC) and remain to be elucidated. By cytological and animal model experiments, this study demonstrated that the expression of lncRNA MNX1-AS1 was remarkably elevated in ICC cell lines and tissues, and was highly and positively correlated with motor neuron and pancreas homeobox protein 1 (MNX1) expression. MNX1-AS1 significantly facilitated the proliferation, migration, invasion, and angiogenesis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 63 publications
(86 reference statements)
0
15
0
Order By: Relevance
“…Growing evidence has exposed that lncRNAs and miRNAs are implicated with multiple cancers including cell growth, survival, differentiation, cell cycle, apoptosis, invasion, and metastasis 10–13 . LncRNAs and miRNAs have also been found to play a regulatory role in the growth, metastasis and progression of ICC, such as lncRNA MNX1‐AS1, 14 lncRNA CCAT1, 15 and lncRNA SNHG3 16 . The previous study showed that lncRNA FAM66C promotes proliferation via the inhibition of the proteasomal pathway in prostate cancer 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence has exposed that lncRNAs and miRNAs are implicated with multiple cancers including cell growth, survival, differentiation, cell cycle, apoptosis, invasion, and metastasis 10–13 . LncRNAs and miRNAs have also been found to play a regulatory role in the growth, metastasis and progression of ICC, such as lncRNA MNX1‐AS1, 14 lncRNA CCAT1, 15 and lncRNA SNHG3 16 . The previous study showed that lncRNA FAM66C promotes proliferation via the inhibition of the proteasomal pathway in prostate cancer 17 .…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA MNX1-AS1 is an antisense RNA of motor neuron and pancreas homeobox protein 1 (MNX1) gene. It has been reported that MNX1-AS1, as an oncogene, promotes the development of many cancers, including intrahepatic cholangiocarcinoma, cervical cancer, lung cancer and hepatocellular carcinoma [ 14 17 ]. In OC, Li et al confirmed that MNX1-AS1 expression is increased in tumor tissues than matched normal tissues, and overexpression of MNX1-AS1 is associated with poor clinical outcomes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Wu et al [ 24 ] suggested that MNX1-AS1 could enhance tumor cell epithelial-mesenchymal transition through upregulating MNX1 expression. Autologously, Li et al uncovered that MNX1-AS1 could also enhance MNX1 transcription, which then activated Ajuba/Hippo signaling pathway in intrahepatic cholangiocarcinoma cells, consequently facilitating tumor progression [ 13 ]. In esophagus cancer, MNX1-AS1 was also demonstrated to facilitate the proliferative and invasive capacities of tumor cells through regulating the miR-34a/SIRT1 signaling axis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…MNX1 antisense RNA 1 (MNX1-AS1) was firstly discovered as a highly expressed gene in colorectal malignant tumor, which is termed CCAT5 as well [12]. Recently, a growing number of studies suggested that MNX1-AS1 was aberrantly expressed in diverse malignancies, including cholangiocarcinoma [13], esophagus cancer [14], breast carcinoma [15][16][17], gastric carcinoma [12,18,19], bladder carcinoma [20], ovarian carcinoma [21,22], cervical cancer [23], osteosarcoma [24,25], laryngeal cancer [26], lung cancer [27][28][29], prostate cancer [30], hepatocellular carcinoma [15], glioblastoma [31] and colon adenocarcinoma [32]. Moreover, aberrant MNX1-AS1 expression has been proposed to correlated with cancer patient survival, indicating its potential as prognostic marker and therapeutic target [12,15,18,23,26].…”
Section: Introductionmentioning
confidence: 99%